FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN PENGGUNA BPJS - Kristianingsih, Yustina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Satisfaction to health services is influenced by several factors such as the physical facility andhealthcare environments, system agreements including waiting time, waiting, as well as the scopeand nature of the health services provided advantages. The phenomenon in the community ofusers still complain BPJS poor service, slow handling, the complexity of procedures to obtainservices. The purpose of this study to identify factors that affect user satisfaction BPJS.The studyused discriptive desing with a sample of 74 respondents BPJS users in RW 05 SawunggalingWonokromo Surabaya with Simple Random Sampling. The variables in this study are the factorsthat affect user satisfaction BPJS.The result of this study showed the majority (97.3%) ofrespondents said the service factor is the factor most affecting user satisfaction BPJS. Importantif BPJS improve management of administrative arrangements to be online, improve the data baseas well as convenience to the terms in the care of membership BPJS order to increase levelsatisfaction.